Differentiating between human and non-human interspecies embryos. Issue 4 (24th May 2013) - MacKellar, Calum
Abstract : Following the debate in the UK House of Lords, in December 2012, uncertainty remains as to the manner in which human and non-human interspecies embryos are differentiated in law.